Pre- and post-headache phases of migraine: multi-country results from the CaMEO – International Study - Richard B. Lipton; Michel Lanteri-Minet; Elizabeth Leroux; Aubrey Manack Adams; Janette Contreras-De Lama; Michael L. Reed; Kristina M. Fanning; Dawn C. Buse (The Journal of Headache and Pain, 2023)
Abstract Background Individuals with migraine frequently experience pre- and post-headache symptoms. This analysis aimed to characterize the relative frequency and burden of pre- and post-headache symptoms in people with migraine using data collected through the Chronic Migraine Epidemiology and Outcomes – International Study. Methods This cross-sectional, observational, web-based survey was conducted in 2021–2022 in Canada, France, Germany, Japan, the United Kingdom, and the United States. Respondents who met modified International Classification of Headache Disorders, 3rd edition, criteria were offered the opportunity to participate. Information collected included migraine-related disability, depression/anxiety symptoms, cutaneous allodynia, activity limitations, and acute treatment optimization. Respondents indicated how often they had pre- or post-headache symptoms using a 5-point scale, ranging from 0 to 4, with a rating of 2 or higher classified as a pre- or post-headache symptom case. Modeling was used to examine relationships with monthly headache days (MHDs) and activity limitations during pre-headache and post-headache phases. Results Among a total of 14,492 respondents, pre-headache symptoms were reported by 66.9%, while post-headache symptoms were reported by 60.2%. Both pre-headache and post-headache symptoms were reported by 49.5% of respondents, only pre-headache by 17.4%, only post-headache by 10.7%, and neither pre- nor post-headache symptoms by 22.4%. Compared with respondents who experienced only pre- or post-headache symptoms, respondents who experienced both pre- and post-headache symptoms had the highest rates of 4–7, 8–14, and ≥ 15 monthly headache days (23.1%, 14.1%, and 10.9%, respectively). Of respondents with both pre- and post-headache symptoms, 58.5% reported moderate-to-severe disability, 47.7% reported clinically significant symptoms of depression, 49.0% reported clinically significant symptoms of anxiety, and 63.8% reported cutaneous allodynia with headache (ASC-12). Moderate-to-severe activity limitations were reported during the pre-headache (29.5%) and post-headache phases (27.2%). For all outcomes modeled, after controlling for covariates, having pre-headache symptoms, post-headache symptoms, or both were associated with worse outcomes than having neither. Conclusions Pre- and post-headache phases of migraine are common, carry unrecognized burden, and may be a target for treatment. Graphical Abstract